Synthesis of benzoyl cyanide through aerobic photooxidation of benzyl cyanide using carbon tetrabromide as a catalyst1. Issue 87 (20th September 2015) - Sugiura, Y.; Tachikawa, Y.; Nagasawa, Y.; Tada, N.; Itoh, A.
<x xml:space="preserve">Abstract</x> We developed a synthetic method toward benzoyl cyanide through aerobic photooxidation of benzyl cyanide in the presence of carbon tetrabromide under visible light irradiation with fluorescent lamps.